Treatment patterns with etanercept and adalimumab for psoriatic diseases in a real-world setting. (October 2013) - Bonafede, Machaon; Johnson, Barbara H.; Fox, Kathleen M.; Watson, Crystal; Gandra, Shravanthi R.
Abstract : Background: This study examined real-world etanercept and adalimumab treatment patterns in patients with psoriasis, psoriatic arthritis, or both. Methods: This retrospective analysis utilized data from patients with psoriasis, psoriatic arthritis, or both from a large, US claims database. Outcome measures included persistence on index therapy; pauses (7–59 days) and gaps (≥60 days) in therapy; and rates of discontinuing, switching and restarting index therapy in nonpersistent patients. Results : Of 4, 453 patients, 2, 534 initiated etanercept and 1, 919 initiated adalimumab. In psoriasis patients ( n = 2, 775), 46.4% and 56.8% on etanercept and adalimumab, respectively, were persistent for ≥12 months, 49.0% and 56.3% discontinued, 23.8% and 22.4% restarted and 14.9% and 11.3% switched index therapy within 12 months. In psoriatic arthritis patients ( n = 1, 197), 60.7% and 63.3% on etanercept and adalimumab, respectively, were persistent for ≥12 months, 48.3% and 51.6% discontinued, 25.8% and 20.0% restarted and 16.5% and 17.9% switched index therapy. In patients with both ( n = 481), 58.1% and 59.6% on etanercept and adalimumab, respectively, were persistent for ≥12 months, 42.7% and 63.2% discontinued, 24.3% and 12.6% restarted and 21.4% and 15.8% switched index therapy. Conclusions : Treatment modifications were common in patients with psoriasis, psoriatic arthritis, or both within 12 months of initiating etanercept or adalimumab.